CHANGEABILITY OF THE RESIDUAL SANITARY-INDICATIVE MICROFLORA OF NATURAL WATER AND SEWAGES AFTER BEAM-OZONE COMBINED PROCESSING - Sklyar, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The ecologically safe technique of the water purification have indicated the following. The frequency of appearance of modifications among representatives of the sanitary-indicative microflora depends on the intensity of disinfection, and it was detected in 56.7% of the tests. As regards the adaptive changes, mostly just one or two features were subjected to them (they were registered in 70.2% and 15.0% of the tests, respectively). Thus, the given physical and chemical agents induce just slight alterations in test cultures’ biological properties. The results obtained at the given stage of detecting the possible phenotypic changes in individual representatives of the sanitary-model microflora in natural water and sewages induced by the beam-ozone combined processing permit us to state that the presented technique of the water disinfection does not injure ecology of the environment.